Beyond the Hit: The Hidden Costs of Repetitive Head Trauma - Sikandar Khan; Lora Talley (Neuroscience Insights)
Repetitive head trauma in sports, particularly concussions, has been strongly associated with neurocognitive impairments, including depression, chronic traumatic encephalopathy (CTE), and altered brain function. These injuries can have significant consequences on major cognitive processes, such as learning and memory. This review synthesizes research that examines the effects of sports-related head trauma, particularly in football, on cognitive functioning. Post-mortem analyses of players across all positions have revealed neuropathological evidence of CTE, including a distinct reduction in hippocampal volume. Notably, episodic memory, a component of declarative memory, is frequently compromised in individuals with CTE. Furthermore, deficits in working memory may contribute to decreased performance during play. Early detection of head trauma and implementation of preventive strategies are crucial for mitigating long-term consequences. While impact-reducing techniques have shown some efficacy in decreasing brain injury incidence, proper tackling techniques, such as “heads-up play,” also play a vital role in minimizing risk. Further research and increased awareness are needed to ensure athletes are fully informed of the potential cognitive risks associated with participation in high-impact sports.